Hubungan Penggunaan Ai-Assistant Dengan Persepsi Kemampuan Kognitif Mahasiswa Dalam Penerjemahan Bahasa Arab - Iqbal Khoirul Muzaky; Fina Aunul Kafi (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2026)
This study aims to determine the correlation between the use of an AI-assistant for translating Arabic texts and students' cognitive abilities in the Arabic Language Education (PBA) Study Program at Al-Falah As-Sunniyah University, Jember. Amid rapid digitalization, students have begun using artificial intelligence as an academic tool, yet its impact on cognitive capacity remains to be empirically tested. The research method employed is a quantitative correlational design, with a sample of 28 students selected via random sampling. Data were collected using a closed-ended questionnaire and analyzed using Spearman’s Rho correlation test via SPSS. The results showed a mean value of 6.78 for the AI-Assistant variable and 8.12 for the cognitive ability variable. The instrument reliability test yielded a Cronbach's Alpha value of 0.970. The correlation analysis produced a coefficient (r) of 0.988 with a significance value (p) < 0.001. This shows a strong, significant positive relationship between the use of an AI assistant and students' cognitive abilities. AI-Assistant does not weaken thinking power but rather functions as a cognitive partner that stimulates students' critical analysis in verifying translation results. These findings recommend the measured integration of AI into the Arabic language learning curriculum in higher education.